PENGARUH KEBAHAGIAAN DI TEMPAT KERJA TERHADAP KINERJA GURU PADA GURU SMA KOTA TERNATE MELALUI KEPUASAN KERJA DAN MOTIVASI KERJA SEBAGAI VARIABEL MEDIASI - Rusli Jafar; Said Hasan; Johan Fahri (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
The general objectives of the study are: to provide new insights for teachers regarding performance that influences teacher happiness so that it can encourage teachers to improve their performance, satisfaction, and motivation. The test tool used is smart partial least square (PLS) as a statistical test tool. The sample in this study amounted to 217 respondents. The results of the study show that: 1) Happiness at work has been proven to have a significant effect on teacher performance, 2) Happiness at work also has a significant effect on job satisfaction, 3) Happiness at work has a significant effect on teacher motivation, 4) Job satisfaction does not have a significant effect on teacher performance in high schools in Ternate City, 5) Motivation has a significant effect on teacher performance. 6) Happiness at work does not have a significant effect on teacher performance through job satisfaction as a mediating variable, and 7) Happiness at work has a significant effect on teacher performance through motivation as a mediating variable